PELATIHAN PENGGUNAAN MEDIA CANVA PADA SISWA DAN PENANAMAN POHON BERSAMA DI SMA NEGERI 1 SIBOLANGIT - Sinaga, Nenni Triana; Simarmata, Juliana; Simarmata, Eno Nopita Sari; Sipayung, Khairunnah; Pakpahan, Safriani Romasta (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
The training on using Canva media for students and the tree planting activity at SMA Negeri 1 Sibolangit aim to enhance students' digital skills and foster awareness of environmental conservation. The Canva training provides students with insights into graphic design and the creation of engaging learning materials, enabling them to develop creativity and improve their understanding of digital technology. Meanwhile, the tree planting activity seeks to instill a sense of environmental responsibility, particularly in preserving nature around the school. The activities include interactive training sessions, hands-on practice in designing Canva, and a tree-planting initiative involving the entire school community. The results indicate that students have become more proficient in using Canva for academic and non-academic purposes and have developed a greater awareness of the importance of greening efforts. Through these activities, students are expected to continue to enhance their digital skills while actively contributing to environmental preservation.